Acquisition of Ca(2+) and HCO3(-)/CO3(2-) for shell formation in embryos of the common pond snail Lymnaea stagnalis - Ebanks, Sue C; O'Donnell, Michael J; Grosell, Martin (Journal of comparative physiology. B, Biochemical, systemic, and environmental physiology, 2010)
Embryos of the freshwater common pond snail Lymnaea stagnalis develop to hatch within 10 days under control conditions (22°C, Miami-Dade tap water) and this development is impaired by removal of ambient calcium. In contrast, embryos did not exhibit dependence upon an ambient HCO(3)(-)/CO(3)(2-) source, developing and hatching in HCO(3)(-)/CO(3)(2-)-free water at rates comparable to controls. Post-metamorphic, shell-laying embryos exhibited a significant saturation-type calcium uptake as a function of increasing ambient calcium concentration. However, changes in ambient bicarbonate concentration did not influence calcium or apparent titratable alkalinity uptake. There was a distinct shift from no significant flux in pre-metamorphic embryos to net uptake of calcium in post-metamorphic stages as indicated by an increased uptake from the micro-environment surrounding the egg mass and increased net uptake in 24-h, whole egg mass flux measurements. Furthermore, HCO(3)(-)/CO(3)(2-) acquisition as measured by titratable alkalinity flux is at least partially attributable to an endogenous carbonate source that is associated with acid extrusion. Thus, calcium requirements for embryonic shell formation are met via uptake but HCO(3)(-)/CO(3)(2-), which is also necessary for shell formation is acquired in part from endogenous sources with no detectable correlation to ambient HCO(3)(-)/CO(3)(2-) availability.